The Effectiveness of Educational Media in Controlling Ergonomic and Psychological Hazards during Work from Home for Lecturers - Shintia Yunita Arini; Putri Ayuni Alayyannur; Dani Nasirul Haqi; Ahmad Fakhri; Ardha Maulana Akbar (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: The number of confirmed cases of COVID-19 continues to increase, so most of the workers in all work sectors are changing to a WFH system. WFH has several impacts related to mental health and musculoskeletal complaints. Therefore, it is necessary to develop educational media for workers who carry out working from home including lecturers. Therefore, this research was conducted with the aim of knowing the relationship between the assessment of the effectiveness of educational media and the increase in knowledge about the ergonomic and psychological hazards during working from home and their control. Methods: This research was an observational study with a cross-sectional study design. The data analysis method used was descriptive semi-quantitative. The population of this research was lecturers in Indonesia. The number of samples using accidental sampling and total sampling was 111 respondents. This research used valid and reliable pre-test and post-test to assess the effectiveness of educational media. Data were analyzed using a paired samples correlation test and Spearman test. Results: There was a significant difference between the results of the pre-test and post-test. In addition, there was a relationship between the assessment of the effectiveness of educational media and changes in post-test scores where for booklet media there was a strong relationship and for video educational media, there was a medium relationship. Conclusion: Based on the results, it can be concluded that there was a relationship between the assessment of the effectiveness of educational media on ergonomic and psychological hazards control during WFH and the increase in knowledge of lecturers in 2021. Keywords: ergonomic hazard, psychology hazard, educational media